Physiological control of cholecystokinin release and pancreatic enzyme secretion by intraduodenal bile acids. Issue 5 (November 1996) - Koop, I; Schindler, M; Bosshammer, A; Scheibner, J; Stange, E; Koop, H
Abstract : BACKGROUND: The physiological relevance of duodenal bile acids in the control of cholecystokinin release and pancreatic enzyme secretion is still unknown. AIMS: To provide a near physiological situation by perfusing a bile acid mixture mimicking the individual endogenous bile acid composition of the person under investigation. For maximal reduction of endogenous bile output the CCK-A receptor antagonist loxiglumide was infused intravenously. SUBJECTS AND METHODS: Seven healthy volunteers were studied on four different days by a duodenal marker perfusion technique. The individual bile acid composition in duodenal juice and test meal stimulated bile acid output was assessed on day 1. Bile acids were perfused at an amount of 30 or 100% as determined on day 1 in combination with the test meal in the presence or absence of loxiglumide. Pancreatic enzymes, bilirubin, and bile acid output were determined in duodenal juice. Plasma cholecystokinin (CCK) and plasma pancreatic polypeptide (PP) were measured radioimmunologically. RESULTS: Bile acid perfusion did not significantly alter stimulated pancreatic enzyme, bilirubin or bile acid output or plasma CCK. Loxiglumide did not alter basal CCK release but increased test meal stimulated CCK output fourfold (p < 0.05). The addition of bile acids to the test meal at a dose resembling 30% of bile acid output as determined on day 1 prevented this increase. Plasma PP concentration remained unchanged by bile acids and were mostly undetectable during loxiglumide infusion. CONCLUSIONS: The CCK producing cell is under constant suppression by intraduodenal bile acids which cannot be further enhanced by a physiological bile acid mixture. However, removal of duodenal bile acids by inhibition of gall bladder contraction unmasks this suppression leading to a dramatic increase in plasma CCK levels. As little as one third of postprandially released bile acids completely reverse this effect. Bile acids are the most important luminal regulator of CCK release in humans.